Identifikasi Tanda Klinis, Prevalensi, dan Faktor Risiko Sporotrikosis pada Kucing Peliharaan di Kota Denpasar - Ryan Aufa Prasetia; Aufa Prasetia, Ryan; Kayati Widyastuti, Sri; Putriningsih, Putu Ayu Sisyawati (Acta VETERINARIA Indonesiana, 2025)
Sporotrichosis is a subcutaneous and systemic mycotic infection affecting humans and animals. It is caused by a pathogenic dimorphic fungus of the genus Sporothrix. This study aimed to identify the clinical signs, prevalence, and risk factors of sporotrichosis in pet cats in Denpasar city. The sample of this study was the skin surface of cats, with a total sample of 101 cats. This study was conducted from November 2024 to January 2025. The examination method was carried out in four ways: physical examination, acetate tape preparation, and impression smear. The collection of skin surface samples was then examined by cytological techniques (Diff-Quik Staining). The results of this study showed that the clinical signs of one sporotrichosis-positive female cat included pruritus with a score of 4/10 in the head, face, and ear areas; the texture of the skin surface was rather rough and dry; there were crusts in the area between the right and left eyes; there was a lot of squama on most of her body's skin; and there was purulent discharge in both nostrils. The prevalence of sporotrichosis in pet cats in Denpasar city was 1%. Statistical analysis showed that factors such as sex, age, breed, husbandry, presence or absence of skin wounds, bathing frequency, and sterilization status were not risk factors for sporotrichosis.